Max Scheler’s Sympathy (Pannakipagrikna) in the Context of Online Education - Almazan, Joeffrey (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This study examines the relevance of Max Scheler’s concept of sympathy in the context of online education by situating it within the Ilocano cultural value of pannakipagrikna, which embodies empathy and emotional sensitivity. Employing a transcendental-phenomenological approach, the research integrates textual analysis of Scheler’s works with semi-structured interviews among Ilocano learners. The findings reveal that pannakipagrikna is expressed through four key themes: pannakaawat (understanding), naimpasnekan a panagdengngeg (active listening), panangtarabay (guidance), and pannakimaysa (emotional unity). These insights highlight the importance of affective and value-based engagement in addressing emotional detachment in online learning. The teacher emerges not merely as a transmitter of knowledge but as a moral and empathetic guide fostering students’ holistic development. The study concludes that contextualizing Scheler’s philosophical anthropology through Ilocano values enriches value-centered pedagogy and broadens the scope of phenomenology beyond Western frameworks.